Cisco voice gateways and gatekeepers - Donohue, Denise (Cisco Press networking technology series., 2006)
Cisco Voice Gateways and Gatekeepers Understanding and configuring GW/GK in complex VoIP networks Denise Donohue, CCIE® No. 9566 David Mallory, CCIE No. 1933 Ken Salhoff, CCIE No. 4915 Deployments of voice over IP (VoIP) networks continue at a rapid pace. Voice gateways are an essential part of VoIP networks, handling the many tasks involved in translating between transmission formats and protocols and acting as the interface between an IP telephony network and the PSTN or PBX. Gatekeepers and IP-to-IP gateways help these networks scale. Gatekeepers provide call admission control, call routing, address resolution, and bandwidth management between H.323 endpoints including Cisco IOS® voice gateways and Cisco® Unified CallManager clusters. IP-to-IP gateways allow VoIP calls to traverse disparate IP networks. Cisco Voice Gateways and Gatekeepers provides detailed solutions to real-world problems encountered when implementing a VoIP network. This practical guide helps you understand Cisco gateways and gatekeepers and configure them properly. Gateway selection, design issues, feature configuration, and security and high-availability issues are all covered in depth. The abundant examples, screen shots, configuration snips, and case studies make this a truly practical and useful guide for anyone interested in the proper implementation of gateways and gatekeepers in a VoIP network. Emphasis is placed on the accepted best practices and common issues encountered in real-world deployments. Cisco Voice Gateways and Gatekeepers is divided into four parts. Part I provides an overview of an IP voice network. Part II is dedicated to voice gateways, including discussions of Media Gateway Control Protocol (MGCP); H.323; Session Initiation Protocol (SIP); voice circuit options; connecting to the PSTN, PBX, and IP WAN; dial plans; digit manipulation; route selection; class of restriction; Survivable Remote Site Telephony (SRST) and MGCP fallback; digital signal processor (DSP) resources; and Tool Command Languaue (Tcl) scripts and Voice XML (VXML). Part III addresses voice gatekeepers, including detailed deployment and configuration. Part IV is dedicated to IP-to-IP gateways. "With this book, the authors provide an in-depth look at the breadth of voice gateway features and capabilities, as well as providing voice gateway configuration guidance."--Christina Hattingh, Access Technology Group, Cisco Systems® Understand the pros and cons of MGCP, H.323, and SIP, how ...